(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The procedures and activities Waste administration refers to the processes that are required to handle rubbish from its inception to its ultimate disposition. This paper discusses about overview of waste management in India, Current status waste management in India, Challenges to effective waste management in India and Waste management generation in India. India confronts significant environmental issues related to waste management, including insufficient trash collection, Transport, cleaning, and removal are all part of the process. The existing waste management systems in India are incapable of dealing with the rising volumes of rubbish produced by a growing urban populace, presenting a hazard to the ecosystem and human safety. A major objective is to move away from reliance on landfills, which offer minimal environmental protection, and toward waste management methods that maintain useable materials inside the economy. Trash separation at the source, as well as the installation of specialised waste treatment plants to extract recoverable materials, play a critical role. These studies will aid future research on the issues of garbage management in India.